2017
DOI: 10.1007/s00431-017-3034-5
|View full text |Cite
|
Sign up to set email alerts
|

Reducing unnecessary chest X-rays, antibiotics and bronchodilators through implementation of the NICE bronchiolitis guideline

Abstract: Implementation of the NICE bronchiolitis guideline supported by a simple educational intervention can effectively reduce the number of inappropriate chest radiographs and antibiotic prescribing in bronchiolitis, and enhance compliance with the NICE guideline. What is Known: • Bronchiolitis management in paediatric units in the UK is variable, with poor evidence for existing guidance. Best available evidence was compiled into the NICE guideline, aiming to standardize care. • Some evidence exists for the effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
1
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 10 publications
2
43
1
3
Order By: Relevance
“…Our rates of CXR use compare favourably with reported benchmarks in the USA of 20–40% but do not meet those achieved by a UK paediatric centre of 4% . Although target rates are difficult to establish, this benchmark study suggests that rates of 4% are achievable and realistic.…”
Section: Discussioncontrasting
confidence: 66%
See 3 more Smart Citations
“…Our rates of CXR use compare favourably with reported benchmarks in the USA of 20–40% but do not meet those achieved by a UK paediatric centre of 4% . Although target rates are difficult to establish, this benchmark study suggests that rates of 4% are achievable and realistic.…”
Section: Discussioncontrasting
confidence: 66%
“…Our rates of CXR use compare favourably with reported benchmarks in the USA of 20-40% 10,14 but do not meet those achieved by a UK paediatric centre of 4%. 11 Although target rates are difficult to establish, this benchmark study suggests that rates of 4% are achievable and realistic. Our study has demonstrated that reducing rates of CXR to this level would be unlikely to lead to any significant missed diagnoses but requires replication in other settings.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Antibiotic treatment does not improve the clinical outcomes of viral infections [31]. Decreasing the use of unnecessary antibiotics is the key to combating AMR, and accurate and rapid diagnosis is crucial to decrease antibiotic prescriptions with a minimized risk [9,10,32]. The present study demonstrates that PCR has higher detectability for respiratory viruses compared to traditional antigen tests and viral cultures.…”
Section: Discussionmentioning
confidence: 70%